Bird remains from the excavations of late medieval HodosivkaRoslavske settlement (Kyiv region, Ukraine) - Tajkova, S.Yu. (Збірник праць Зоологічного музею, 2016)
The bird remains obtained during the excavations of the medieval settlement Hodosivka-Roslavske (XI/XII–XIVth cent. AD) were analyzed. Five hundred seventy four bones (of total 795 specimens) were identified as belonging to 12 species. Twenty seven bones were identified to genus level only (Anas sp.). Besides, 221 bones are highly fragmented for the proper identification of their species affiliation. The identified bone fragments collected from the same layer were grouped by the number of source specimens. The majority of the processed remains are belonged to Mallard (Anas platyrhynchos). All other species are represented by a handful number of bone remains (except for the Garganey Anas guerguedula, Shoveler Anas clypeata and Gadwall Mareca strepera).